Induction of 5-aminolevulinate synthase by activators of steroid biosynthesis - Martini, Claudia Noemí (2007)
Different cytochromes P450 are involved in steroid biosynthesis. These cytochromes have heme as the prosthetic group. We previously reported that ACTH, an activator of glucocorticoid biosynthesis in adrenal, requires heme biosynthesis for a maximal response. In the present study, we investigated the effect of ACTH, and the effect of two activators of the adrenal mineralocorticoid synthesis, endothelin-1 and low sodium diet on 5-aminolevulinate-synthase (ALA-s) mRNA. ALA-s is the rate-limiting enzyme in heme biosynthesis. It was found that infusion of rats with ACTH for 1 h caused an increase of adrenal ALA-s mRNA and activity accompanied by an increase in plasma corticosterone. CYP21, a cytochrome involved in the synthesis of both corticosterone and aldosterone, was not modified at the RNA level in adrenal glands by 1 h of ACTH infusion. Consistently, infusion of endothelin-1 for 1 h increased ALA-s mRNA and aldosterone content in adrenal gland without modifying CYP21 mRNA levels. To study if ALA-s is also regulated by the main physiological stimuli that increase adrenal mineralocorticoid secretion, we fed rats with low salt diet for 2 or 15 days. Low salt diet treatment increased adrenal gland ALA-s mRNA levels. On the other hand, the rapid stimulation of ALA-s mRNA by ACTH which acts through cyclic AMP was confirmed in H295R human adrenocortical cells, the only human adrenal cell line that has a steroid secretion pattern and regulation similar to primary cultures of adrenal cells. Our findings suggest that the acute activation of adrenal steroidogenic cytochromes by trophic hormones involves an increase in heme biosynthesis which will favor the production of active cytochromes.